Storage and fresh cut radish - doi: 10.4025/actasciagron.v35i2.15461 - Ricardo Antonio Ayub; Bruna Spinardi; Mariane Gioppo (Acta Scientiarum. Agronomy, 2012)
The aim of this work was to ascertain the post-harvest preservation of Crimson Giant radishes with the following conditions: 1) stored at room temperature (20 ± 2°C and 75% relative humidity; RH) with or without leaves; or 2) stored at a refrigeration temperature of 5ºC and 90% RH with leaves, without leaves or minimally processed. For radishes stored at room temperature, evaluations were made at 0, 1 and 3 days. For radishes stored at a refrigeration temperature, evaluations were made at 0, 1, 3 and 6 days. The parameters evaluated included weight loss, pulp firmness, soluble solids, pH, and titratable acidity. At room temperature (20 ± 2°C and 75% RH), the radish bulbs with and without leaves had weight losses exceeding 5% after one day of storage, which rendered these radishes unmarketable. Minimally processed radish bulbs can be stored for more than six days at a temperature of 5ºC, and non-processed radishes stored with and without leaves at the same temperature should not be stored for more than one day.